การควบคุมความแม่นยำของการจำลองเชิงเวลาของวงจรสายส่งโดยการประมาณค่าการกระจายแรงดันและกระแสในสายด้วยฟังก์ชันเลขชี้กำลังแบบแบ่งท่อน - ภาณุวัฒน์ ด่านกลาง (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
This research proposes a new method for transient simulation of transmission lines circuit. This method not only gives the time domain solution of the line terminal voltage and current, but also their distributions within the lines. The method achieves its goal by treating the distributions as Distributed State Variables (DSV) and transforms the transmission lines equation into an ordinary differential equation. This allows the lines to be treated as a single component that behaves like other lumped dynamic components. Using Backward Differentiation Formulae for time discretization, the line is converted to a time domain companion model, from which its local truncation error for time step control can be derived. As the voltage and current distributions get more complicated with time, a new piecewise exponential approximation with controllable accuracy is invented. A segmentation algorithm is also devised so that the line is dynamically bisected to guarantee that the total approximation error is a small fraction of the local truncation error. Using this approach, the user can see the line voltage and current at any point and time freely without explicitly segment the line a priori before starting the simulation. The MATLAB is used to test 5 examples which show good agreement with Hspice.